Sosialisasi Bahaya Merokok dan Napza Terhadap Generasi Muda di Mts Muhammadiyyah Maligi - Hambali; Chandra, Muhammad; Yendri, Afiftra; Praneza, M. Iqbal; Hanafi, Indra; Habibi, Fadil (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2024)
The purpose of this study was to evaluate how well MTS Muhammadiyah Maligi students have been socialized about the risks associated with smoking, drugs, alcohol, and other addictive substances (NAPZA). This socialization program was created to provide adolescents with a thorough understanding of the adverse effects of drug and cigarette use, given the increasing incidence of these behaviors in this age group. This research utilizes a qualitative methodology that combines participatory observation and in-depth interview methods. The research findings show that students' knowledge and awareness of the risks associated with drug use and smoking have significantly improved after the implementation of the socialization program. In addition, their attitudes towards initiatives to stop the use of illegal drugs have also improved. In short, this socialization was successful.